In Whose Interest? The Early Years of the First Caisse Populaire, 1900‑1945 - Rudin, Ronald (Historical Papers / Communications historiques)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1987)
AbstractIn 1900 Alphonse Desjardins opened the first caisse populaire at Lévis, a small town located across the St. Lawrence from Quebec City. Many historians have seen the establishment and the early operations of the Caisse populaire de Lévis in heroic terms, as it proved to be the beginning of the development of a vast cooperative movement. Desjardins and his colleagues were described as disinterested men only desirous of providing financial services to the poor. This characterization has a certain validity, as credit was made available that could not have been found elsewhere. Nevertheless, such a perspective ignores the fact that the founders of the caisse and their successors were members of the local petite bourgoisie who were profoundly insecure regarding their place in an industrializing Quebec. As a result, the operations of this caisse up to the end of World War II were not always in the best interests of the poorer elements of Lévis.